Dietary Polyphenols in Cancer Chemoprevention: Implications in Pancreatic Cancer - Anita Thyagarajan; Andrew S. Forino; Raymond L. Konger; Ravi P. Sahu (Antioxidants, 2020)
Naturally occurring dietary agents present in a wide variety of plant products, are rich sources of phytochemicals possessing medicinal properties, and thus, have been used in folk medicine for ages to treat various ailments. The beneficial effects of such dietary components are frequently attributed to their anti-inflammatory and antioxidant properties, particularly in regards to their antineoplastic activities. As many tumor types exhibit greater oxidative stress levels that are implicated in favoring autonomous cell growth activation, most chemotherapeutic agents can also enhance tumoral oxidative stress levels in part via generating reactive oxygen species (ROS). While ROS-mediated imbalance of the cellular redox potential can provide novel drug targets, as a consequence, this ROS-mediated excessive damage to cellular functions, including oncogenic mutagenesis, has also been implicated in inducing chemoresistance. This remains one of the major challenges in the treatment and management of human malignancies. Antioxidant-enriched natural compounds offer one of the promising approaches in mitigating some of the underlying mechanisms involved in tumorigenesis and metastasis, and therefore, have been extensively explored in cancer chemoprevention. Among various groups of dietary phytochemicals, polyphenols have been extensively explored for their underlying chemopreventive mechanisms in other cancer models. Thus, the current review highlights the significance and mechanisms of some of the highly studied polyphenolic compounds, with greater emphasis on pancreatic cancer chemoprevention.